Negotiation skills - Eunson, Baden (Milton, Qld : John Wiley and Sons, 1994)
This book is divided into two parts: Negotiation: What is it?; Strategies and Tactics.
Keywords: Business; Negotiation; Negotiation in business; Negotiation